Stanisław Lisiecki (1872-1960): szkic biograficzny = Stanisław Lisiecki (1872-1960): a biographical sketch - Mróz, Tomasz (1975- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
S. Lisiecki`s most complete biography so far is presented in this paper. He was a classics scholar, translator of works of Greek philosophers and a dissenter from Catholicism. The text is based mostly on archival sources of the Archive of the Polish Academy of Sciences, Jagiellonian Library and private collections.
Keywords: Lisiecki, Stanisław (1872-1960); Plato (filozof; 427 p.n.e.-347 p.n.e.); Arystoteles (filozof; 384 p.n.e.-322 p.n.e.); historia filozofii; historia studiów klasycznych; history of philosophy; history of classical studies